Analysis of Interfaith Marriage Law in the Marriage Law and Law Number 23 of 2006 concerning Population Administration Perspective - Idham Payapo; Wahda Z. Imam; Suwarti Suwarti (Syntax Corporation Indonesia, 2023)
-